2010
DOI: 10.1017/s0030605310000013
|View full text |Cite
|
Sign up to set email alerts
|

Population status and distribution of freshwater turtles in Taiwan

Abstract: Because of burgeoning demand in the Chinese market and extensive habitat loss more than half of the freshwater turtle and tortoise species in Asia are categorized as Endangered or Critically Endangered on the IUCN Red List. To investigate the distribution and status of the native freshwater turtle species of Taiwan a trapping programme was conducted during 2001–2007, yielding a total of 1,828 individuals of four native species at 103 sites. Mauremys sinensis was the most abundant and widely distributed species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Ades et al (2000) and Bhupathy et al (2000) noted that M. reevesii was one of the commonest species seen in the food markets of China, Hong Kong, and Taiwan in the 1970s and early 1980s, but that they disappeared almost completely after the influx of turtles from other Asian countries. Recent surveys have revealed that this turtle is quite common on Kimmen Island, a small island off the coast of Taiwan Lue et al 1999), but may be rare on Taiwan itself Chen and Lue 2010). In Hong Kong and other parts of China the species was previously considered a common species, but is now infrequently recorded Lau and Shi 2000).…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Ades et al (2000) and Bhupathy et al (2000) noted that M. reevesii was one of the commonest species seen in the food markets of China, Hong Kong, and Taiwan in the 1970s and early 1980s, but that they disappeared almost completely after the influx of turtles from other Asian countries. Recent surveys have revealed that this turtle is quite common on Kimmen Island, a small island off the coast of Taiwan Lue et al 1999), but may be rare on Taiwan itself Chen and Lue 2010). In Hong Kong and other parts of China the species was previously considered a common species, but is now infrequently recorded Lau and Shi 2000).…”
Section: 3mentioning
confidence: 99%
“…-In the 20th Century, several authors documented that M. reevesii was abundant in various areas of continental China (e.g., Sowerby 1925;Pope 1935;Liu and Hu 1940) and Taiwan (e.g., Mao 1971). However, judging from the fact that this turtle is disappearing from markets in continental China and the island of Taiwan Lue et al 1999;Lau and Shi 2000;Chen and Lue 2010;R. Aoki, pers.…”
Section: 3mentioning
confidence: 99%
“…Recently, mammalogists discovered a dense population of Eurasian otter (Lutra lutra) on the island, which is extremely rare in the neighboring region and has been extirpated in Taiwan (Hung et al 2004). Chen and Lue (2010) discovered stable populations of the Chinese pond turtle (Chinemys reevesii), which was also extirpated in Taiwan. The large Kinmen wetland now sustains one of the largest wintering populations of Great Cormorants (Phalacrocorax carbo) in East Asia (Chang et al 2008).…”
Section: Python Increases Were Associated With the Withdrawal Of Milimentioning
confidence: 99%
“…As a trade center between Taiwan and China, this region is notorious as a route for the illegal wildlife trade, including large numbers of yellow-margined box turtles (Cuora flavomarginata) and other herpetofauna for the pet trade (Chen and Lue 2010). Considering that pythons have rapidly invaded the state of Florida in the US, local people soon concluded that the presence of pythons was the result of introductions by pet traders.…”
Section: Introductionmentioning
confidence: 99%
“…Demand for turtles has increased as the income of people has improved, and this has encouraged farmers to initiate more breeding farms over the past 20 years. As a lowland aquatic animal (Chen and Lue, 2010), turtles are mainly cultured in southern China, where ground water is abundant and agricultural land is limited (Shi et al, 2008). Farmers in this area are commonly using concentrated turtle aquaculture operations to solve the problem of low land availability.…”
Section: Introductionmentioning
confidence: 99%